Pengaruh Digital Marketing Terhadap Brand Awareness Podcast Berbahasa Jawa: Pengaruh Digital Marketing Terhadap Brand Awareness Podcast Berbahasa Jawa - Jatmiko, Faza Kharga (The Commercium, 2022)
Until now, technology has grown rapidly and has produced business tools for business people to increase brand awareness of a product to consumers. One of them is the Mendoan Podcast, which uses a digital marketing strategy to increase brand awareness among consumers or their listeners. The main purpose of this research is to find out whether there is an influence between "Digital marketing on Brand awareness of Javanese Podcasts". This research uses a quantitative approach by using a survey method or method. The sampling method used is the purposive sampling method with illustrations of 100 respondents who have been identified as listeners and follow Mendoan’s Instagram Podcast. The method of collecting information is by sowing a questionnaire link through a Google form which is distributed online and calculating the information score using a Likert scale. Analysis of research data conducted by the author is a simple linear regression analysis technique in order to determine the effect of variable X (Digital Marketing) on variable Y (Brand Awareness). Based on the results of the linear regression test conducted by the researcher, it can be seen that the digital marketing variable has a correlation value of 0.416 on Brand Awareness with an effect of 17.3%. So that it shows that there is a significant positive influence between digital marketing on brand awareness.